1977
DOI: 10.3758/bf03198741
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying the slant aftereffect

Abstract: Transfer of the median plane slant aftereffect was assessed across changes in the type of depth information for the slant of the display. In addition, the effectiveness of monocularpictorial and binocular information in inducing the aftereffect was measured. Binocular information produced a larger aftereffect than did monocular-pictorial information, and adaptation created with one type of depth information induced an aftereffect assessed with presentation of the other type of depth information. The results su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

1983
1983
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
1
11
1
Order By: Relevance
“…Our conclusions support the evidence that stereo-depth and stereo-slant adaptation occur mainly at the perception level (Balch et al, 1977;Duke & Wilcox, 2003). Our results seem to be in contradiction with the results of Berends and Erkelens (2001), who concluded that adaptation to disparity signals can occur with perceptual metamers.…”
Section: Present Results and Existing Researchcontrasting
confidence: 78%
See 2 more Smart Citations
“…Our conclusions support the evidence that stereo-depth and stereo-slant adaptation occur mainly at the perception level (Balch et al, 1977;Duke & Wilcox, 2003). Our results seem to be in contradiction with the results of Berends and Erkelens (2001), who concluded that adaptation to disparity signals can occur with perceptual metamers.…”
Section: Present Results and Existing Researchcontrasting
confidence: 78%
“…Stereoscopic after-effects have further been attributed to down weighting or even suppression of the disparity cue due to conflicts between disparity and the monocular cues (Burian, 1943;Burian & Ogle, 1945;Miles, 1948). Finally, stereoscopic after-effects may result from perceived depth biases (Balch, Milewski, & Yonas, 1977;Duke & Wilcox, 2003). Thus, adaptation may occur at all stages of stereodepth processing from the encoding of binocular disparity to the final depth percept.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Frisby, 1979;De Valois & De Valois, 1988;Spillman & Warner, 1990;Wandell, 1995). Under these several assumptions, Coltheart (1971), Balch et al (1977), and Poom and Bö rjesson (1999) attributed SAE to neural units selectively sensitive to slant, namely slant detectors. In their interpretation, the slant detectors were assumed to change their response characteristics as a result of prolonged exposure to a slanted surface, and this modification in response characteristics was supposed to be the basis of SAE.…”
Section: Figmentioning
confidence: 99%
“…Second, during an observation of a surface, the impression of slant can change even if the impression of tilt is maintained (Bergman & Gibson, 1959;Smith, 1965). Third, prolonged observation of a surface orientation can induce the aftereffect of slant (Kö hler & Emery, 1947;Bergman & Gibson, 1959;Wenderoth, Rodger & Curthoys, 1968;Wenderoth, 1970;Balch, Milewski & Yonas, 1977;Poom & Bö rjesson, 1999). Bergman and Gibson (1959) studied an aftereffect specific to surface slant (slant aftereffect, SAE) under the following procedure.…”
Section: Introductionmentioning
confidence: 99%